2020
DOI: 10.1080/02699931.2020.1803217
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of trait anxiety on visual working memory, as a function of task demand and situational stress

Abstract: Higher trait anxiety can impair cognitive functioning via attention, but relatively little is known about the impacts on visual working memory. These were investigated using previously validated visual feature binding tasks. In Study 1, participants' memory for visual features (shapes) and feature bindings (coloured shapes) was assessed. Stimulus presentation was simultaneous or sequential, varying attentional demand, and participants were grouped according to trait cognitive anxiety (low, moderate, high). No … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
23
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(28 citation statements)
references
References 67 publications
(167 reference statements)
3
23
1
Order By: Relevance
“…Trait somatic anxiety was found to significantly predict perceived cognitive difficulty specifically with language and verbal memory. While some recent evidence suggests that trait somatic anxiety can indeed negatively affect visual working memory (Spalding et al, 2021), spatial working memory (Vytal et al, 2013), and processing speed (Schoen and Holtzer, 2017), the present results are somewhat unexpected in the context of ACT (Eysenck et al, 2007). One possible explanation for this outcome is that trait somatic anxiety also demands attention.…”
Section: Trait Anxiety and Cognitive Difficultycontrasting
confidence: 72%
See 3 more Smart Citations
“…Trait somatic anxiety was found to significantly predict perceived cognitive difficulty specifically with language and verbal memory. While some recent evidence suggests that trait somatic anxiety can indeed negatively affect visual working memory (Spalding et al, 2021), spatial working memory (Vytal et al, 2013), and processing speed (Schoen and Holtzer, 2017), the present results are somewhat unexpected in the context of ACT (Eysenck et al, 2007). One possible explanation for this outcome is that trait somatic anxiety also demands attention.…”
Section: Trait Anxiety and Cognitive Difficultycontrasting
confidence: 72%
“…However, they also examined a potential interaction effect between anxiety and situational stress (by threat of electric shock and ego-threat instructions). Spalding et al (2021) also used the STICSA to assess the impact of anxiety on visual working memory, finding that while both dimensions of trait anxiety affected performance efficiency, only trait somatic anxiety predicted performance accuracy. Schoen and Holtzer (2017) used the Beck Anxiety Inventory (BAI; Beck et al, 1988), which, like the STICSA, is a measure of daily life, and found somatic, but not cognitive anxiety, to be associated with cognitive performance in older adults.…”
Section: Trait Anxiety and Cognitive Difficultymentioning
confidence: 99%
See 2 more Smart Citations
“…However, recently, it has been argued that anxiety should be further separated into the dimensions of cognitive anxiety; anxiety symptoms related to thought processes, and somatic anxiety; anxiety related to physiological symptoms [11]. Recent studies have suggested that these dimensions differently impact performance on cognitive tasks [14][15][16]. For instance, anxiety inductions that induce anxiety through physiological anxiety symptoms, such as the 7.5% CO 2 Challenge, due to inducing an unconditioned anxiety response [17,18], have been argued to disrupt face-recognition accuracy to a larger magnitude than cognitive anxiety inductions.…”
Section: Moderators Impacting Effect Anxiety On Face-recognition Accuracymentioning
confidence: 99%